KRITERIA CURAH HUJAN SEBAGAI PARAMETER IKLIM DI PERAIRAN CILACAP - Lusiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2018)
The objective to be achieved in this paper is to know the criteria of rainfall which is one of the climatic parameters that occur in Cilacap waters (low, medium, high, very high criteria). The method in this study is a combination of survey and literature review. In this study the authors take the location in the waters of Cilacap. The data used are secondary data obtained from the Central Bureau of Statistics of Cilacap Regency. The data sample used is statistical data within 5 year period starting from 2012 until 2016. Based on data analysis that has been done, that is grouping or classification of the biggest rainfall data in the period of 5 years (2012-2016) obtained by detailed data that is : In 2012 the largest monthly rainfall occurred in November of 124.0 mm including the middle criteria; In 2013 the largest monthly rainfall occurred in June of 96.6 mm which included low criteria; By 2014 the largest monthly rainfall occurs in July at 194.0 mm which includes medium criteria; By 2015 the largest monthly rainfall occurs in December of 132.0 mm which includes medium criteria; In 2016 the largest monthly rainfall occurs in October of 181.0 mm which includes medium criteria. Based on the details of the data, it can be concluded that the largest monthly rainfall as a parameter of climate in Cilacap waters is included in the middle criteria.